Effects of Psychiatric Hospital Closures on Local Jail Administrators, Correctional Staff, and Inmates - Lasko, Mark Christian (2019)
A series of psychiatric hospital closures has led to a movement of care for individuals with mental illness from state-run facilities to managed care centers. Many of the individuals who no longer reside in psychiatric hospitals have become ensnared in the criminal justice system. Correctional facilities have an increased burden to care for the needs of the mentally ill, but lack the training and facilities to do so adequately. In this study, the lived experiences of correctional staff who have experienced the process of a hospital closure were examined. Psychiatric rehabilitation and gatekeeper theories served as the theoretical framework for the study. Data were collected using focus group interviews with 17 correctional officers and individual interviews with 3 administrative staffers at a jail in a southern U.S. state. Data were recorded and transcribed and then analyzed for themes. Six themes emerged: (a) open the psychiatric hospital back up, (b) training, (c) they don't need to be here, (d) mental health housing/they can't function in general population, (e) public awareness, and (f) they didn't think it through. Analysis of study data resulted in the identification of several gaps in community supports that can improve the lives of mentally ill individuals. These include avoiding future hospital closures, improving correctional mental health bed space, and providing correctional-specific training for staff at the jail. The study has positive social change implications for both correctional staff and mentally ill inmates in that the study can inform the improvement of officer training and the development of new community supports, which can reduce negative outcomes for mentally ill individuals